Perspektywy Członkowstwa Turcji w Unii Europejskiej - Reimisz, Liliana (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The paper, entitled The prospects of Turkish membership in EU, presents an international debate that has continued for many years, concerning the subject of Turkish EU candidature. The debate is an expression of European elites’ anxiety about the future shape of the organization. The study deals with such issues as a common European identity and Turkey’s Europeanization process, from Atatürk’s reforms up to the integration with European structures. This paper is based on the assumption that, in line with the rival opinions of supporters and opponents of Turkish admission to EU, two models of Europe can be identified: the exclusive model and the multicultural (open) model.